The Cost of Misguided Urbanization: The Case of Informal Settlements in Butuan City, Philippines - Ma. Kresna D. Navarro; Catherine Roween C. Almaden (Academic Journal of Interdisciplinary Studies, 2014)
The informal settlements in Butuan City, Philippines pose the intractable problem of housing and providing services for the urban poor. They exact tremendous costs to government infrastructure projects and the city as a whole. In this study, these costs are accounted for, particularly the costs the government will incur to compensate them for being displaced in the implementation of public infrastructure project. Primary data were collected through inventory of losses (IOL), socio-economic survey (SES) and the replacement cost surveys. Secondary data were obtained through key informant interviews with different stakeholders. The paper quantifies the costs of compensating them through replacement of their affected resources and providing resettlement. It also establishes different types of compensation to secure just terms for all parties. It presents a rich picture of how the informal settlers affect urban environment and the monetary and operational challenges they pose to the government and the society at large.
Keywords: O17; R51; 330; Informal Settlements; Social Cost; Urbanization